2012
DOI: 10.1038/ncb2423
|View full text |Cite
|
Sign up to set email alerts
|

CLASPs prevent irreversible multipolarity by ensuring spindle-pole resistance to traction forces during chromosome alignment

Abstract: Loss of spindle-pole integrity during mitosis leads to multipolarity independent of centrosome amplification 1-4 . Multipolar-spindle conformation favours incorrect kinetochore-microtubule attachments, compromising faithful chromosome segregation and daughter-cell viability 5,6 . Spindle-pole organization influences and is influenced by kinetochore activity 7,8 , but the molecular nature behind this critical force balance is unknown. CLASPs are microtubule-, kinetochore-and centrosome-associated proteins whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 40 publications
5
90
1
Order By: Relevance
“…3A), unless accompanied by an increase in DNA content (Freije et al, 2012), we hypothesized that the differentiation observed in Clasp2KD mouse keratinocytes stemmed from a mitotic defect leading to a DNA content increase. This is in line with the well-defined role of Clasp2 in the control of mitotic fidelity (Logarinho et al, 2012;Maia et al, 2012;Mimori-Kiyosue et al, 2006;Pereira et al, 2006).…”
Section: Clasp2 Expression Ensures Mitotic Fidelity In Primary Mouse supporting
confidence: 54%
See 1 more Smart Citation
“…3A), unless accompanied by an increase in DNA content (Freije et al, 2012), we hypothesized that the differentiation observed in Clasp2KD mouse keratinocytes stemmed from a mitotic defect leading to a DNA content increase. This is in line with the well-defined role of Clasp2 in the control of mitotic fidelity (Logarinho et al, 2012;Maia et al, 2012;Mimori-Kiyosue et al, 2006;Pereira et al, 2006).…”
Section: Clasp2 Expression Ensures Mitotic Fidelity In Primary Mouse supporting
confidence: 54%
“…Mammalian Clasps (Clasp1 and Clasp2) are widely conserved MT plus-end-binding proteins that mediate MT stabilization (Akhmanova et al, 2001). In the context of mitosis, elegant reports have uncovered that CLASPs are fundamental for MT-kinetochore attachment, maintenance of spindle bipolarity, accurate chromosome segregation and spindle pole integrity, thereby preventing aneuploidy (Logarinho et al, 2012;Maia et al, 2012;MimoriKiyosue et al, 2006;Pereira et al, 2006). We have recently described that Clasp2 is largely confined to the basal progenitor layer of the epidermis, decorating the MT ends at cell adhesion sites (Shahbazi et al, 2013;Shahbazi and Perez-Moreno, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, changing the balance of forces within the spindle alters the cellular requirements to establish and/or maintain bipolarity. Likewise, both ninein and CLASPs are required for spindle bipolarity by generating forces at the spindle poles that counteract the forces generated at the chromosomes by Kid and CENP-E during chromosome alignment [98]. Because of the MT nucleation capacity of extra centrosomes, centrosome amplification might change this fine balance, thus rendering cells with extra centrosomes more sensitive to proteins involved in maintaining spindle and kinetochore-MT tension.…”
Section: Coping With Centrosome Amplification: Sticking Togethermentioning
confidence: 99%
“…4B). In order to prevent spindle multipolarity, the activity of some PCM components, such as ninein, Cep90 (the largest isoform of PIBF1) and Cep57, is coordinated to facilitate the bundling and stabilizing of centrosomal microtubules and to withstand microtubule tensions (Kim and Rhee, 2011;Logarinho et al, 2012;Wu et al, 2012). Furthermore, both Plk1 and AurA are essential kinases for the construction of robust focused spindle poles (Fig.…”
Section: Multipolar Spindle Formationmentioning
confidence: 99%